Hostility vs. Reluctance: Implication of Nuclear Posture Adoption towards India's Bilateral Relations with Pakistan and China - Aristawidya, Kinanti; Syawfi, Idil (Parahyangan Center for International Studies, 2023)
This paper examines India's different nuclear posture adoption toward Pakistan and China. India has been developing its nuclear weapons to ensure its survival amidst ongoing tensions with Pakistan and China. However, India's relationship with China tends to be cooperative, while Pakistan tends to be conflictual. Theoretically, the mutual accumulation of nuclear power will increase tension and further deteriorate bilateral relations. Through posture optimization theory and Jervis' four worlds, this article qualitatively compares the two cases and its implication for their bilateral relations. The result shows that India's adoption of an assured retaliation posture that directly deters Pakistan affects their relationship to be hostile and leaves no possibilities for cooperation. On the contrary, the existence of the United States as India's strategic partner made China reluctant to be aggressive and opt for diplomatic settlements with India. India-Pakistani relations dynamics reflect Jervis's doubly dangerous world, while Sino-Indian relations reflect the second world unaffected by the accumulation of power, although there is an intense security dilemma. Keywords: India; Pakistan; China; Nuclear Posture; Nuclear Policy